Redox-responsive probes for selective chelation of bivalent cations - Noureddine Raouafi; Janet Bahri; Rihab Sahli; Khaled Boujlel (QScience Connect, 2012)
N,N-disubstituted bis(furanyl-2-methyl)aminoanilines are new electrochemically-active probes for cations relying on the phenylenediamine moiety as an electroactive transducer and the difuranylamino group as an ionophore site. The electrochemical investigations, by means of cyclic and Osteryoung square wave voltammetries (CV and SWV, respectively), showed that these compounds are able to bind Mg2+, Ca2+, Ni2+ and Zn2+ cations with strong affinities. The addition of catalytic amounts of trifluoromethanesulfonic acid (TfOH) was found necessary to achieve rapid cation complexation. The electroactive redox features of the probes were drastically modified when the ionophore site was bonded to the cations. The anodic potential shifts of the oxidation peaks were between 905 and 1030 mV depending on the cations.